Dietary intake of animal-based products and likelihood of follicular lymphoma and survival: A population-based family case-control study - Odutola, Michael K.; van Leeuwen, Marina T.; Bassett, Julie K.; Bruinsma, Fiona; Turner, Jennifer; Seymour, John F.; Prince, Henry Miles; Milliken, Samuel T.; Hertzberg, Mark; Roncolato, Fernando; Opat, Stephen S.; Lindeman, Robert; et al. (Frontiers in Nutrition, 2023)
Background: The association between dietary intake of foods of animal origin and follicular lymphoma (FL) risk and survival is uncertain. In this study, we examined the relationship between dietary intake of dairy foods and fats, meat, fish and seafoods, and FL risk and survival. Methods: We conducted a population-based family case-control study in Australia between 2011–2016 and included 710 cases, 303 siblings and 186 spouse/partner controls. We assessed dietary intake of animal products in the year before last using a structured food frequency questionnaire and followed-up cases over a median of 6.9 years using record linkage to national death data. We examined associations with FL risk using logistic regression and used Cox regression to assess association with all-cause and FL-specific mortality among cases. Results: We observed an increased FL risk with increasing daily quantity of oily fish consumption in the year before last (highest category OR=1.96, CI=1.02-3.77; p-trend 0.06) among cases and sibling controls, but no associations with spouse/partner controls. We found no association between FL risk and the consumption of other types of fish or seafood, meats or dairy foods and fats. In FL cases, we found no association between meat or oily fish intake and all-cause or FL-specific mortality. Conclusion: Our study showed suggestive evidence of a positive association between oily fish intake and FL risk, but findings varied by control type. Further investigation of the potential role of environmental contaminants in oily fish on FL etiology is warranted.